Portrayals of corporate social responsibility: A comparative analysis of a Russian and a Canadian newspaper - Julia Rozanova (Journal for East European Management Studies, 2006)
The general public learns about the social role of corporations from the media, yet little research has been conducted into the media portrayals of corporate social responsibility, particularly in the post-communist countries. Analysis revealed that in both countries corporate social responsibility was portrayed from the perspectives of the enterprises, the state, and the civil society. While there were similarities in the depictions of types of social activity undertaken by corporations in the two countries, significant differences emerged as well. The influence of the state was emphasized in the Russian articles, while the Canadian articles focused on the role of the civil society. The paper places the findings in the theoretical context of the social role of business in different institutional settings, and points out directions for further research into the media representation of corporate social responsibility. – – Die Öffentlichkeit hört über die soziale Rolle der Aktiengesellschaften aus den Medien, es wurden jedoch nur wenige Forschungen im Bereich der Darstellung durch die Medien durchgeführt, insbesondere in ehemalig kommunistischen Ländern. Analysen enthüllten dass in Russland und Kanada die soziale Verantwortung Aufgabe der Unternehmen, des Staates und der Zivilgesellschaft war. Es gab Gemeinsamkeiten, aber auch Unterschiede in den Typen der sozialen Betätigung. Der Einfluß des Staates wurde in den russischen Artikeln betont, wohingegen die kanadischen Artikel die Rolle der Zivilgesellschaft hervorhoben. Der Aufsatz platziert die Ergebnisse im theoretischen Kontext der sozialen Rollen von Unternehmen und weist auf weitere Forschungen in der Medienrepräsentation von sozialer Verantwortung von Aktiengesellschaften hin.
Keywords: 650; Corporate social responsibility; media portrayals; Russia; Canada